RELEVANSI KEMANDIRIAN FISKAL: SEBUAH TINJAUAN - Septian Asriadi Putra; Verri Riyanto; Annisa Rachman Supartono; Josephine Immanuel; Ikram Azhar Hagi; Mochamad Andi Nurfauzi (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2024)
Since the enactment of Decentralization in Indonesia, there have been policy changes, one of which is finance. The central government makes financial transfers to local governments to carry out policies according to authority. However, this scheme leaves the problem of economic dependence on local governments. So an indicator is given, namely the Regional Fiscal Authority Index. Previous literature found that many local governments are still at a low level of independence. Furthermore, there is still debate about whether this independence can affect development achievements. For this reason, a study was conducted using spatial analysis and panel data regression to identify the effect of fiscal independence on development outcomes. It was found that most regions still have low fiscal independence and low human development outcomes in regencies and cities in West Java Province. Interestingly, a different pattern was found between regions located at the border and industrial centers with other regions. This study concludes that the location of city districts can also affect fiscal independence and does not always go hand in hand with development achievements. Furthermore, independence needs to be followed by proper financial management.